Liquid-assisted grinding and ion pairing regulates percentage conversion and diastereoselectivity of the Wittig reaction under mechanochemical conditions - Denlinger, Kendra Leahy; Ortiz-Trankina, Lianna; Carr, Preston; Benson, Kingsley; Waddell, Daniel C.; Mack, James (Beilstein Journal of Organic Chemistry, 2018)
Mechanochemistry is maturing as a discipline and continuing to grow, so it is important to continue understanding the rules governing the system. In a mechanochemical reaction, the reactants are added into a vessel along with one or more grinding balls and the vessel is shaken at high speeds to facilitate a chemical reaction. The dielectric constant of the solvent used in liquid-assisted grinding (LAG) and properly chosen counter-ion pairing increases the percentage conversion of stilbenes in a mechanochemical Wittig reaction. Utilizing stepwise addition/evaporation of ethanol in liquid-assisted grinding also allows for the tuning of the diastereoselectivity in the Wittig reaction.
Keywords: green chemistry; high-speed ball milling; HSBM; LAG; liquid-assisted grinding; Wittig

(untitled) - Do, J.-L.; Friščić, T. (ACS Cent. Sci., 2017)

(untitled) - James, S.; Adams, C.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Takacs, L. (Chem. Soc. Rev., 2013)

(untitled) - Boldyreva, E. (Chem. Soc. Rev., 2013)

(untitled) - Strukil, V. (Beilstein J. Org. Chem., 2017)

(untitled) - Metro, T.-X. M.; Martinez, J.; Lamaty, F. (ACS Sustainable Chem. Eng., 2017)

(untitled) - Do, J.-L.; Friščić, T. (Synlett, 2017)

(untitled) - Achar, T. K.; Bose, A.; Mal, P. (Beilstein J. Org. Chem., 2017)

(untitled) - Zhao, S.; Li, Y.; Liu, C.; Zhao, Y. (Tetrahedron Lett., 2018)

(untitled) - Tan, D.; Friščić, T. (Eur. J. Org. Chem., 2018)

(untitled) - Strukil, V. (Synlett, 2018)

(untitled) - Intasa-ard, S. G.; Imwiset, K.; Bureekaew, S.; Ogawa, M. (Dalton Trans., 2018)

(untitled) - Hernandez, J. G. (Chem. – Eur. J., 2017)

(untitled) - Geciauskaite, A. A.; Garcia, F. (Beilstein J. Org. Chem., 2017)

(untitled) - Andre, V.; Quaresma, S.; Ferreira da Silva, J. L.; Duarte, M. T. (Beilstein J. Org. Chem., 2017)

(untitled) - Balema, V.; Wiench, J.; Pruski, M.; Pecharsky, V. (J. Am. Chem. Soc., 2002)

(untitled) - Balema, V.; Wiench, J.; Pruski, M.; Pecharsky, V. (Chem. Commun., 2002)

(untitled) - Cristau, H.-J. (Chem. Rev., 1994)

(untitled) - Murphy, P.; Lee, S. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - Hajos, G.; Nagy, I. (Curr. Org. Chem., 2008)

(untitled) - Fairlamb, I. (ChemSusChem, 2009)

(untitled) - Marsden, S. (Nat. Chem., 2009)

(untitled) - Schlosser, M. (Top. Stereochem., 1970)

(untitled) - Vedejs, E.; Peterson, M. (Top. Stereochem., 1994)

(untitled) - Vedejs, E.; Peterson, M. (Adv. Carbanion Chem., 1996)

(untitled) - Shearouse, W.; Mack, J. (Green Chem., 2012)

(untitled) - El-Anwnr, I. M.; Foad, I. Z. S. A. A. (J. Mater. Sci. Technol., 1995)

(untitled) - Pearson, R. G. (J. Am. Chem. Soc., 1963)

(untitled) - Jones, G.; Dole, M. (J. Am. Chem. Soc., 1929)

(untitled) - Jenkins, H. D. B.; Marcus, Y. (Chem. Rev., 1995)